Occurrence of Body Posture Abnormalities in Overweight and Obese Children Aged 5-6 Years-Pilot Study - Alicja Bober; Aleksandra Kopaczyńska; Agnieszka Puk; Agnieszka Chwałczyńska (MDPI AG, 2024)
Objectives: The study aimed to assess the occurrence of body posture disorders and their changes under the influence of a physioprophylactic program in children depending on body weight. Methods: In the examined children, the general and segmental body composition and body posture were determined using a physiotherapeutic assessment based on the Kasperczyk method. Mass, overall, and segmental body composition were determined using the bioelectrical impedance method using a TANITA body composition analyzer. The study group of 76 children was divided due to body weight disorders into Group I (n = 51), in which BMI and fat mass values were within the normative limits for age and gender, and Group II (n = 19), comprising children whose body weight exceeded the norm and/or fat mass exceeded normative values. The examined children underwent a physioprophylactic. The program was conducted by qualified physiotherapists for 12 weeks, once a week for 30 min. The therapeutic program was focused on physioprevention of being overweight and the correction of body posture. Results: A distal distribution of fat mass was observed in the examined group. Asymmetry in the sagittal plane was found in 35% of children. No statistically significant differences were found in the presence of asymmetry in the sagittal plane between the groups. No statistically significant differences were found in the occurrence of posture irregularities between the groups. Conclusions: There were no changes in the weight and body posture of the examined children under the influence of the physiotherapy program. The lack of correlation in the examined group between body weight and posture irregularities in 5-6-year-olds may suggest the acquisition of posture defects as a consequence of the persistence of overweight or obesity.